Civil Codification in Peru: Some Critical Considerations - León Hilario, Leysser (2004)
This paper presents a critical analysis of the process of civil codification in Peru. To this end, the author analyses three relevant aspects of this problem: the approach or general vision of codification, the legislative technique and the working method. With regard to the initial point, it is asserted that a code must reflect the social reality, be aligned with the needs of this reality, and avoid becoming a mere instrument of academic debate. With regard to the legislative technique, the importation of foreign norms that are not compatible with the local context is questioned. Consequently, the integration of foreign legislation should be conducted with an understanding of the objectives and context in which they were created, and with an adaptation to the judicial reality of the receiving country. Finally, the methodology employed in the codification process is discussed. The author posits that a fragmented approach, wherein a specialist is tasked with drafting a specific section of the code without contributing to other parts of the codification process, results in inconsistencies that ultimately impact the organic coherence of the final text. In conclusion, the analysis presented demonstrates the necessity for a civil codification that is adapted to the social reality, and which is developed through an integral and coherent process that responds to the needs of Peruvian society.